2022
DOI: 10.3390/ijerph191912022
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Individual and Group Level Factors on the Level of Rural Residents’ Domestic Waste Sorting: Evidence from Shaanxi, China

Abstract: Rural residents are the main agents of rural domestic waste-sorting; their level of sorting directly relates to the improvement of their rural living environment and the construction of “beautiful countryside”. Considering the data of 943 rural residents in Shaanxi Province, China, this study incorporates the factors at the individual and group levels and explores how personal norms and mianzi, which is the individual’s reputation and social status, at the individual level and social capital at the group level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In rural China, which has been a typical acquaintance society since ancient times, social networks are formed through kinship, blood and local ties, and cultures such as human kindness and face( mianzi ) are deeply rooted in the soil of the vernacular social network and have an important influence on the functioning of the rural social ecology ( 48 ). It was shown that social networks can increase rural residents' familiarity, reduce uncertainty in making behavioral decisions, and increase their level of domestic waste separation ( 49 51 ). In addition, the social network formed by the cadre-mass relationship can also enhance the flow and exchange of information and increase the level of trust among each other, thus promoting the participation of rural residents in rural environmental governance ( 52 ).…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…In rural China, which has been a typical acquaintance society since ancient times, social networks are formed through kinship, blood and local ties, and cultures such as human kindness and face( mianzi ) are deeply rooted in the soil of the vernacular social network and have an important influence on the functioning of the rural social ecology ( 48 ). It was shown that social networks can increase rural residents' familiarity, reduce uncertainty in making behavioral decisions, and increase their level of domestic waste separation ( 49 51 ). In addition, the social network formed by the cadre-mass relationship can also enhance the flow and exchange of information and increase the level of trust among each other, thus promoting the participation of rural residents in rural environmental governance ( 52 ).…”
Section: Theoretical Hypothesismentioning
confidence: 99%